PRODUCT INNOVATION STRATEGY AND ITS IMPACT ON SME COMPETITIVENESS IN THE ERA OF THE DIGITAL ECONOMY - Yussi Ramawati; Harmiaty Bahar; Muh. Husriadi (Adisam Publisher, 2025)
This research examines product innovation strategies and their impact on the competitiveness of small and medium enterprises (SMEs) in the food and beverage sector in Kendari City, in the context of the digital economy. The aim of this research is to explore effective innovation strategies, analyze the impact of innovation on increasing competitiveness, and evaluate available support and resources. The research method uses mixed methods with survey design and in-depth interviews. The respondents were 50 small and medium businesses in the food and beverage industry in Kendari City. The research results show that the use of digital technology and the frequency of product development are key factors that help increase the competitiveness of SME businesses. In addition, external government support and access to financial resources greatly influence SMEs' ability to innovate. The implications of this research indicate the need for policies that support the integration of digital technology into SME innovation strategies and increase access to external resources and support.